An Analysis of Narratives Representing Women’s Agency and Role in the Public Space in Najd in the Nineteenth and Early Twentieth Centuries - Alazaz, Hanan (UI Scholars Hub, 2025)
This paper is a review and analysis of historical narratives and poems to propose a framework of the agency of women in one of the most conservative regions in Arabia in the nineteenth and early twentieth centuries, Najd. These narratives include examples of recorded historical oral accounts and poems by women that exhibit women’s contribution to the public life and participation in the decision-making within their tribal communities. The narratives and literature discussed in the paper reflect these women’s involvement in the fields of education, politics, trade and military activity. Moreover, a reading of poetry that broadcasts their resistance to what they perceive as the bondage of marriage unravels stereotypical views of these women as being voiceless. The contextualized reading of these narratives suggests that women had agency and independence within the norms of their culture. It serves as a tool to envision the trajectory of women’s empowerment in Saudi Arabia through reading the past and understanding the cultural structures from which the narratives emerge.